Лазерна локація супутників ЛЛС "Львів-1831" - Білінський, А.; Апуневич, С.; Благодир, Я.; Вовчик, Е.; Вірун, Н. (Праці наукового товариства ім. Шевченка, 2011)
The current status and capabilities of one of the geodetic techniques satellite laser ranging is presented The Lviv astronomical observatory satellite laser ranging station is described within the international network The main scientific research areas and their results are presented .